PEMANFAATAN APLIKASI KAHOOT SEBAGAI MEDIA PEMBELAJARAN PAI SISWA KELAS VIII PADA MASA PANDEMI DI SMP NEGERI 3 KARANG BAHAGIA BEKASI - Permata, Diah Dewi; Rukajad, Ajad; Herdiana, Yayad (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2024)
The emergency coronavirus outbreak has resulted in the government taking several policies to overcome the outbreak, one of which is in the education sector in the form of distance learning. However, PJJ raises many problems, such as inappropriate learning methods and media. This is under the results of learning evaluations carried out on PAI subjects. This phenomenon is a special attraction for researchers to raise the theme of this research. The research aims to provide a complete picture of the appropriate use of learning media in the PJJ process through the Kahoot application media. The research method currently used is a qualitative approach with data sources including PAI teachers, school principals, some students, and related parties, the methods used are interviews, observation, and documentation analysis, the locus of this research is SMPN 3 Karang Bahagia. The results of the research can be presented as follows: 1) With the implementation of PJJ, the use of the Kahoot application media is considered effective in PAI subjects, 2) The use of the Kahoot application media provides a solution to the PJJ problems faced by students and teachers, 3) With the development of technology-based industrial revolution 4.0, utilizing the Kahoot application as a learning medium is considered appropriate. So this research can have implications for increasing the effectiveness of PAI learning, providing alternative distance learning, increasing student involvement in the learning process, increasing teacher creativity, optimizing the use of learning media, developing learning content, especially for Class VIII students at SMP Negeri 3 Karang Bahagia and so on.